Group Counseling with Self Management Techniques: Effective Strategies for Reducing Nomophobia Among Adolescents - Dian Ari Widyastuti; Siti Muyana (Universitas Ahmad Dahlan, 2019)
This study aims to determine the effectiveness of group counseling with self-management techniques to reduce nomophobia among adolescents. This study is a quantitative research with experimental research type and one group pretest-posttest design. The subjects in this study were 8 Vocational High School students in Yogyakarta City, Indonesia. Data collection in the study used the nomophobia scale instrument. The study used the Wilcoxon test to analyze research data. Based on the results of data analysis, it can be concluded that group counseling with self-management techniques is effective in reducing nomophobia among adolescents, especially students of Vocational High Schools in Yogyakarta, Indonesia. School counselors can use the results of the study as a reference to help students reduce nomophobia through group counseling with self-management techniques.